2000
DOI: 10.1021/jo991761r
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Substituted Benzyldiphenylphosphine Oxides

Abstract: Photochemical reactions (lambda irr = 254 nm) of substituted benzyldiphenylphosphine oxides 1a-e have been investigated in benzene and acetonitrile. alpha-Cleavage from the singlet excited state is proposed as the primary process, and products formed both before and after escape of the primary intermediates from the solvent cage result. Radicals 2 and 3 are observed by nanosecond flash photolysis following excitation of 1a at 266 nm in acetonitrile. Acetone sensitization of 1a,b fails to improve the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Formation of unidentified products of coupling of the radical pair by attack of the phosphinoyl radical at the ring carbons of the naphthyl ring may occur. Indeed, a recent paper reports the coupling at the ortho and para carbons as well as the benzylic carbon for the radical pair [Ph 2 P(O) • • CH 2 Ph] that is formed photolytically from Ph 2 P(O)CH 2 Ph. The formation of side products and the trapping of radical diffusion products by benzene solvent on photolysis of 1 (Ar = Ph) was discussed in an earlier paper .…”
Section: Discussionmentioning
confidence: 99%
“…Formation of unidentified products of coupling of the radical pair by attack of the phosphinoyl radical at the ring carbons of the naphthyl ring may occur. Indeed, a recent paper reports the coupling at the ortho and para carbons as well as the benzylic carbon for the radical pair [Ph 2 P(O) • • CH 2 Ph] that is formed photolytically from Ph 2 P(O)CH 2 Ph. The formation of side products and the trapping of radical diffusion products by benzene solvent on photolysis of 1 (Ar = Ph) was discussed in an earlier paper .…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and Neckers studied the photochemistry of benzyldiphenylphosphine oxides and found that the photochemistry proceeds via the singlet excited state to yield products from both solvent cage and cage escape processes. 46 The radicals obtained from cleavage of the excited state species were both observed by nanosecond laser flash photolysis (Scheme 4.10). The photochemistry is being investigated in terms of its application to photoinitiation and protecting group chemistry.…”
Section: Scheme 318mentioning
confidence: 99%